New guidelines for the diagnosis of epidermolysis bullosa. (28th February 2020) - Has, C.; Liu, L.; Bolling, M.C.; Charlesworth, A.V.; El Hachem, M.; Escámez, M.J.; Fuentes, I.; Büchel, S.; Hiremagalore, R.; Pohla‐Gubo, G.; van den Akker, P.C.; Wertheim‐Tysarowska, K.; et al.
Summary: Epidermolysis bullosa (EB) is a group of rare inherited disorders in which the skin is more fragile than usual, and outside forces like minor injury or rubbing cause blisters or ulcers that may be slow to heal and often leave scars. EB comprises four main types, with more than 30 subtypes. The diagnosis is based on clinical manifestations, meaning how it looks, mode of inheritance, level of skin splitting and the genetic defect. A group of experts from countries all over the world developed these guidelines on behalf of the charity DEBRA International, to provide information on the laboratory diagnosis of EB. Publications (i.e. scientific studies about EB that had been published in journals) were identified in public databases. Sixty‐four papers were appraised, and their quality rated. Based on this, the authors recommend the following: If EB is suspected, laboratory diagnosis is always required, after informed consent. If available and affordable, both genetic (DNA) testing and analysis of a skin sample (by a process called immunofluorescence) should be performed to allow complete diagnosis. However, this is not always possible. Prioritisation can shorten the time to diagnosis and save resources but requires expertise. For example, in a new‐born, analysis of a skin sample should be the first diagnostic step since it delivers the results within a few days. In parallel, genetic testing should always be performed. If the EB type can be clinically recognized or the disease is mild, genetic testing by a process called next‐generation sequencing is recommended, because no valuable information is expected by analysis of the skin. If the genetic defect is detected in one affected person, parents and other family members can be tested for confirmation and genetic counselling. If no genetic defect is detected, research methods must be employed, or the diagnosis reconsidered. Precise diagnosis of EB enables early prediction of the disease severity and its management, genetic counselling and prenatal diagnosis, and inclusion in therapy trials. This is a summary of the study: Clinical practice guidelines for laboratory diagnosis of epidermolysis bullosa Abstract : Linked Article: Has et al. Br J Dermatol 2020; 182 :574–592